Envisioning Entrepreneurship's Future: Introducing Me-Search and Research Agendas. (September 2021) - Shepherd, Dean A.; Wiklund, Johan; Dimov, Dimo
The future of the field of entrepreneurship is bright primarily because of the many research opportunities to make a difference. However, as scholars how can we find these opportunities and choose the ones most likely to contribute to the literature? This essay introduces me-search and a special issue of research-agenda papers from leading scholars as tools for blazing new trails in entrepreneurship research. Me-search and the agenda papers point to the importance of solving a practical problem; problematizing, contextualizing, and abstracting entrepreneurship research; and using empirical theorizing to explore entrepreneurial phenomena.